Implementation and consolidation of courses to educators’ training for rural education: A systematic review - Gomes, Darlene Araújo (2022)
This research set out to investigate, through Systematic Literature Review (RSL) in the “CAPES Periodicals”, what are the main challenges encountered in the implementation and consolidation processes of Licenciature Rural Education (LEdoC) in the country. In this survey, filters were made: at first with the descriptors; then the peer-reviewed article texts; and, being located using the ScIELO and the DOAJ directories, in order to filter data and scrutinize the object to be investigated. The results showed an increase in research on the subject and the many challenges posed to the LEdoC consolidation, such as: internal dispute in universities, difficulty in understanding the course proposal by its executors, difficulty in materializing the alternation, and also establishing a posture of resistance due to the current political moment experienced by Brazilians, which greatly affect education, and consequently, the LEdoC.